An exploratory and descriptive study on how Jacob Zuma is represented as a toxic leader in visual text: The Sunday Times Case Study - Masemola, Sibongile (The IIE, 2017)
President Jacob Zuma’s governance has been faced with challenges such as a volatile political, economic and social landscape which has consequently been the subject of satirical narratives in national newspapers. It seems as South Africa’s political, economic and social climate suffers, the presidents brand image transforms to one that is ‘toxic’ as featured in news reports and illustrated in satirical cartoons. Satirical cartoons are a vehicle used to highlight and communicate topical or controversial issues about the state of a country and may employ agenda-setting and framing strategies to substantiate depictions. The focus of this research paper, as well as the primary research question, is to explore how President Jacob Zuma is represented as a toxic leader in satirical cartoons as featured in The Sunday Times newspaper. The primary aim of the paper is to explore semiotic language to determine the presence of any representations that signify toxic leadership towards President Jacob Zuma in political cartoons and how his brand image may be influenced. In order to explore how President Jacob Zuma is represented as a toxic leader in visual text, as well as interpret how his brand image may be influenced as a consequence, the researcher has used a mixed methods content analysis. This will allow the researcher to analyse data through the quantification of data in the form of a tally table which was measured against eight dimensions from Pelletier’s (2010) typology of toxic leadership and behaviours. For the qualitative aspect of the data analysis, thematic analysis was used to identify the emergence of representations from the satirical cartoons through observation of the text. Barthes Model of Levels of Meaning (Abdul-Jabbar, 2014) was used to support the thematic analysis and provide context. The findings of this study reveal that President Jacob Zuma is not depicted as a toxic leader in the Sunday Times satirical cartoons. The President however was represented as an incompetent, selfish leader who lacks ‘real’ authoritative leadership as per the themes identified in the cartoons, thus influencing the Presidents brand image to match the themes.
Keywords: Brand Image; Personal Branding; Political Leadership; Politics; Branding; Toxic Leadership; Visual Communication